2022
DOI: 10.1002/jbt.23150
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0088196 suppresses trophoblast migration and invasion by the miR‐525‐5p/ABL1 axis and the PI3K/AKT signaling pathway

Abstract: Our study aimed to explore the role of circ_0088196 (circular TNC [circTNC]) in trophoblast invasion and migration in preeclampsia (PE) both in vitro and in vivo. CircTNC, miR‐525‐5p, and ABL1 expression in trophoblast HTR8/SVneo cells were evaluated by quantitative real‐time polymerase chain reaction (qRT‐PCR). Cell viability, migration, and invasion were detected by Cell Counting Kit‐8 (CCK‐8), wound healing, and Transwell assays. The binding between circTNC (or ABL1) and miR‐525‐5p was validated by RNA pull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…CircRNAs have crucial regulating effects in PE by acting as miRNA sponges. 14,16,26 Tan et al reported that hsa_circ_0001326 regulates trophoblast cell function via absorbing miR-186-5p. 19 In this study, based on the microarray analysis and target prediction, we identified two candidate miRNAs, miR-630 and miR-145-5p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CircRNAs have crucial regulating effects in PE by acting as miRNA sponges. 14,16,26 Tan et al reported that hsa_circ_0001326 regulates trophoblast cell function via absorbing miR-186-5p. 19 In this study, based on the microarray analysis and target prediction, we identified two candidate miRNAs, miR-630 and miR-145-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) is an endogenous non‐coding RNA molecule, which has the characteristics of high stability and tissue specificity 12 and can act as sponge molecules of microRNAs (miRNAs) to regulate their target genes 13 . A lot of studies have found that the abnormal expression of circRNA could interfere with trophoblast cell function and thus affect the progression of PE 14–17 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation